Occurrence and biological outlines of two speciesof Scylla (De Haan) in Chilika lagoon, India - Mohanty, S K; Mohapatra, A; Mohanty, Rajeeb K; Bhatta, K S; Pattnaik, A K (Indian Journal of Fisheries, 2011)
The mud crab population in Chilika lagoon was hitherto considered as belongingto a single species of Scylla serrata. The present study, after examiningcolouration, reticulation on limbs, size range, minimum size at first maturity,habitat preference, fishery season, breeding and morphological traits, confirmedthe co-existence of two species, Scylla tranquebarica (Fabricius,1798) and Scyllaserrata (Forsskal,1755) in Chilika lagoon. The maximum size ofÂ  Scyllatranquebarica (240mm / 2.8kg) and Scylla serrata (181mm / 0.83kg) recordedduring the study were considered as the largest sizes so far recorded from Indianwaters. Collection and estimation of landing statistics separately for two mudcrab species from a single water body seemed to be the first attempt in thecountry. Scylla serrata and Scylla tranquebarica accounted for 81.52 and 18.48%share respectively in the average annual landing. Strategic conservationregulation need to be formulated for mud crab fishery in Chilika lagoon basedon species-wise landings and biological information to prevent unregulated exploitation.